2005
DOI: 10.1017/s0020859005002087
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenean Marriage Strategies in the Nineteenth Century: The French Basque Case

Abstract: Marriage strategies in the rural Basque country of the nineteenth century differed according to social background and gender. Propertied families had more diversified strategies than landless families as a result of persistent single inheritance practices, population growth, urbanization, and industrialization which generated massive emigration. Propertied families helped some of their children to settle in local rural villages and others to emigrate to cities (women) or to America (men). Landless families, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A woman who had the status of potential heiress would prefer to remain unmarried rather than wed a man beneath her in the village social hierarchy. 27 A servant at least got paid for the same kind of labour that the wife of a poor man performed unpaid. A servant might, eventually, retire back to the family farmstead, as all offspring of the basseria had the right to do if they had not cashed in their inheritance.…”
Section: Servants and The Hunt For A Basque Mythologymentioning
confidence: 99%
“…A woman who had the status of potential heiress would prefer to remain unmarried rather than wed a man beneath her in the village social hierarchy. 27 A servant at least got paid for the same kind of labour that the wife of a poor man performed unpaid. A servant might, eventually, retire back to the family farmstead, as all offspring of the basseria had the right to do if they had not cashed in their inheritance.…”
Section: Servants and The Hunt For A Basque Mythologymentioning
confidence: 99%
“…The culture imposed traditional values upon the family in order to support the survival of the house; meaning the interests of the house prevailed over the interests of the individual members of the household. In order to preserve their ancient single inheritance practices and preserve this system, the first-born male or female child, who would marry the non-inheriting son or daughter of a family of similar background, would then settle in the heir's family house creating a multigenerational family unit (Arrizabalaga, 2005).…”
Section: Fundingmentioning
confidence: 99%
“…Many studies have indicated the prevalence of socioeconomic homogamy in pre-industrial societies, especially among landholding farmers (e.g. Arrizabalaga 2005;Bras and Kok 2005;Bull 2005;Dribe and Lundh 2005;Van Leeuwen and Maas 2002). At least to some extent this could be viewed as an indication of the strategic and instrumental nature of pre-industrial marriages (cf.…”
Section: Marriage Migration and Social Mobilitymentioning
confidence: 99%